Baby-box schemes in England: parent and practitioner experiences, and recommendations - Helen L. Ball; Catherine E. Taylor (BMC, 2020)
Abstract Background Programmes offering carboard baby boxes to parents in England began in some NHS Trusts in 2016. This study aimed to examine the strengths and weaknesses of English baby-box schemes as experienced by healthcare providers and parents. Methods An independent mixed-methods evaluation was conducted via telephone interviews and online surveys with healthcare providers and parents in all 7/9 NHS regions of England where baby-box schemes were established 2016-2019. Participants responded to requests circulated electronically by NHS Research & Design Departments, and infant health organisations in England. The objectives were to identify how parents and healthcare providers understood and experienced baby-box schemes implemented in England to date, and to produce recommendations for organisations considering involvement in future schemes. Results Baby-box schemes changed over time, and were complex to run and monitor. Both parents and practitioners were misinformed about their purpose and origins. Partnerships with a commercial box-provider reduced the investment needed to run a baby-box scheme, and offered potential benefits to staff regarding engagement with families via online education and face-to-face contact around handover of boxes, but carried unforeseen costs. Of particular concern was the box-provider's access to parent personal details being promoted by NHS staff and parents' lack of awareness; the hidden costs incurred by NHS facilities of running a box-scheme; and the costs incurred by parents in accessing their 'free' box. Sixteen recommendations are proposed for healthcare providers and organisations considering commercial - health-provider baby-box partnerships in future. Conclusions Many assumptions exist about the origins and purpose of baby-boxes; this misinformation needs correcting, especially as it relates to infant death reduction and safe infant sleep. Baby-box schemes take multiple forms from those motivated by social welfare to those motivated by commercial profit. The English experience of partnership schemes between healthcare facilities and commercial box-providers reveals some success stories, along with multiple points of ambiguity, unanticipated difficulty, and concerns for infant safety.